ANALISIS RISIKO KARAKTERISTIK, SOSIAL EKONOMI, PERILAKU DAN FAKTOR LINGKUNGAN TERHADAP MALARIA (Studi Kasus di Kecamatan Arongan Lambalek Kabupaten Aceh Barat) - Susy Sriwahyuni Sukiswo; Rinidar Rinidar; Sugito Sugito (Jurnal Pendidikan Kimia (JPKim), 2015)
AbstractMalaria is an infectious disease remains that has become a global concern. Arongan Lambalek sub district was an endemic area of malaria in West Aceh regency. It was in Medium Incidence Area category with Annual Parasite Incidence (API) value of 3,67 per 1000 population. This case was still above the target of National API elimination phase that was less than 1 per 1000 population in 2013. The study was conducted in Drien Rampak Community Health Center Work Area in Arongan Lambalek of Aceh Barat Regency with the purpose to know the relationship of characteristic, socioeconomic, behavioral and environmental factors and determine the most dominant variable that influence the malaria incidence in Arongan Lambalek sub district of Aceh Barat District. This study was an analytical observational study with case-control approach. Samples were taken by using purposive sampling method with a total sample of 66 respondents, consisting of 33 cases and 33 controls that met the inclusion and exclusion criteria, in this term, case group comprised of people who tested positive for malaria while control group comprised of people who tested negative for malaria based on laboratory tests/RDT (rapid diagnostic test). The results of the bivariate analysis using Chi Square test it was found that there were five variables associated with the incidence of malaria in Arongan Lambalek sub district of Aceh Barat Regency, such occupation (p = 0,000; OR= 0,048), knowledge (p= 0,000; OR= 17,50), attitude (p= 0,001; OR= 7,429), precaution (p= 0,000; OR= 9,80) and the environment (p= 0,000; OR= 9,0). Based on the multivariate logistic regression analysis, the most dominant variable on the incidence of malaria was knowledge about the malaria (p= 0,006; OR= 12,78; 95% CI = 2,045-79,893). It is recommended that further analysis on behavioral factors should be carry out, especially in knowledge in relation to the incidence of malaria in Aceh Barat District.Keywords : Malaria, Socio economic, behavioral, Environment